STRATEGY FOR THE DEVELOPMENT OF SUPERIOR MADRASAH BY BUILDING TEACHER'S COMMITMENT TO THE ORGANIZATION - Widat, Faizatul; Fauzi, Ahmad; Saleha, Latifatus (Universitas Nurul Jadid, 2022)
This study aims to determine the form of a superior madrasah development strategy by creating teacher commitment in madrasah. The approach used in this research is a qualitative case study type approach. The informants of this study were the head of the madrasa, the deputy head of the madrasa, teachers and employees of the Miftahul Islam Elementary School. While the data collection methods used are interviews, observation and documentation. The study results show that: first, Madrasah Ibtidaiyah Miftahul Islam involves a strategy for developing madrasas by building teacher commitment; second, the head of the madrasa has a plan for developing superior madrasas by making teacher commitment through; Leader Is Exemplary, Reward and Punishment and Continous improvement.